Stock Valuation Of Pt Unilever Indonesia Tbk: Assessing Financial Impact Of Economic And Industry Pressures In The Fmcg Sector - Astrid Laregan Jota; Erman Arif Sumirat; Subiakto Sukarno (Riviera Publishing, 2025)
This study examines the financial performance and stock valuation of PT Unilever Indonesia Tbk (UNVR.JK) amid mounting economic and competitive challenges in Indonesia's fast-moving consumer goods (FMCG) sector from 2020 to 2024. Unilever Indonesia, a market leader in household and personal care products, experienced deteriorating financial performance during this period, evidenced by declining revenue, profit margins, and market valuation. Macroeconomic pressures, including inflation, rupiah depreciation, rising operating costs, and shifting consumer preferences, have directly affected profitability and investor confidence. The company's net profit declined from IDR 5.8 trillion in 2021 to IDR 3.4 trillion in 2024, and its revenue dropped from IDR 38.6 trillion to IDR 35.1 trillion. The results indicate that although Unilever Indonesia has strong brand equity and a nationwide distribution network, the company suffers from supply chain inefficiencies, a high dependency on imported raw materials, and a limited ability to respond to rapidly evolving consumer behavior. Its market share has significantly declined, exacerbated by geopolitical boycotts and intensifying competition from nimble local companies such as Indofood CBP, Kino, and Mayora Indah. Macroeconomic variables, particularly inflation and exchange rate volatility, were found to have a statistically significant influence on financial performance and stock price volatility. Valuation analysis reveals that Unilever's intrinsic value, estimated through Discounted Cash Flow and Dividend Discount Model, exceeds its current market price. This indicates potential undervaluation if the company achieves operational improvements and strategic realignment. Based on these findings, the strategic recommendations proposed are diversifying the supply chain to reduce exposure to imported inputs, accelerating digital transformation across marketing and distribution, expanding into high-growth categories aligned with health and wellness trends, strengthening risk management frameworks to hedge macroeconomic shocks, and restructuring cost base to improve long-term profitability .